Evaluating the Outcomes of Brief Experimental Analyses at Two Points in Time - Butterfuss, Reese M. (My University, 2015)
Reading is a fundamental skill for success in school. Thus, providing effective intervention to children underperforming in a standard classroom is critical. Our study explores differences in the outcomes of brief experimental analyses (BEAs) when administered at two different times during the school year to see how children's instructional needs may change. We found that BEA outcomes differed for most children in our sample when administered at two different times, perhaps as a function of changes in students' academic skills. Our results may shed light on how often instruction needs to change in schools to meet the changing academic needs of students.
Color poster with text, graphs, tables, and charts.
Keywords: Brief experimental analysis; Reading instruction; Posters